Hairy Root Transformation: A Useful Tool to Explore Gene Function and Expression in Salix spp. Recalcitrant to Transformation - Gomes, Carolina; Dupas, Annabelle; Pagano, Andrea; Grima-Pettenati, Jacqueline; Paiva, Jorge Almiro P. (Frontiers in Plant Science, 2019)
Willow (Salix spp. L.) species are fast-growing trees and shrubs that have attracted emergent attention for their potential as feedstocks for bioenergy and biofuel production, as well as for pharmaceutical and phytoremediation applications. This economic and environmental potential has propelled the creation of several genetic and genomic resources for Salix spp. Furthermore, the recent availability of an annotated genome for Salix purpurea has pinpointed novel candidate genes underlying economically relevant traits. However, functional studies have been stalled by the lack of rapid and efficient coupled regeneration-transformation systems for Salix purpurea and Salix spp. in general. In this report, we describe a fast and highly efficient hairy root transformation protocol for S. purpurea. It was effective for different explant sources and S. purpurea genotypes, with efficiencies between 63.4% and 98.7%, and the screening of the transformed hairy roots was easily carried out using the fluorescent marker DsRed. To test the applicability of this hairy root transformation system for gene functional analysis, we transformed hairy roots with the vector pGWAY-SpDRM2, where the gene SpDRM2 encoding a putative Domain Rearranged Methyltransferase (DRM) was placed under the control of the CaMV 35S constitutive promoter. Indeed, the transgenic hairy roots obtained exhibited significantly increased expression of SpDRM2 as compared to controls, demonstrating that this protocol is suitable for the medium/high-throughput functional characterization of candidate genes in S. purpurea and other recalcitrant Salix spp.